Pengaruh Kegiatan Senam Fantasi Terhadap Perkembangan Motorik Kasar Pada Anak Umur 3-4 Tahun Di Pos Paud Bina Pergiwati Kemlayan Surakarta Tahun Pelajaran 2015/2016 - Setyawati, Win Yunidar (2016)
Background problem in this research is a movement that is usually taught the teachers are too complicated, and monotonous because it mimics gymnastic movements that exist on tape and less precisely the stimulus provided by the teacher. The purpose of this study was to determine the effect fantasy gymnastics activity against gross motor development in children aged 3-4 years in early childhood POS Bina Pergiwati Kemlayan Surakarta academic year 2015/2016. This study uses a Pre-Experimental Design (Pre-Experimental Designs) is the Group One Prates-Postes (The one group pretest-posttest). Data collection techniques in this research observation and documentation. Data analysis that compares the magnitude of "t" obtained after the calculation (to = 10.7778). It can be seen that to greater than tt, namely: 2.26 <10.7778> 3.25. Due to greater than tt then the hypothesis is rejected, the proposed Zero conclusion experimental results conclusively be said to be gymnastic fantasies can affect the child's gross motor development